BRAND AMBASSADOR AND BRAND IMAGE ON PURCHASING DECISIONS WITH WOM AS AN INTERVENING VARIABLE IN ONLINE SHOP SHOPEE ON COLLEGE STUDENTS IN KERINCI DISTRICT AND SUNGAI PENUH CITY: INDRA BUDAYA - Budaya, Indra (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2024)
The aim of this research based on the problems above is to find out whether brand ambassadors and brand image have a positive and significant influence on e-WOM in decisions. The object of this research is all students in Sungai Banyak City and Kerinci Regency with a total of 50 respondents. The results of this research are that Brand Ambassadors have a direct influence on purchasing decisions as evidenced by the results of (0.001 < 0.05) and the calculated t value < t table (3.733 > 2.01063), Brand Image does not have a direct influence on purchasing decisions as evidenced by the results of 0.892 > 0.05 and t count < t table (0.137 < 2.01063), Brand Ambassador has no influence on WOM (Word Of Mouth) as evidenced by the results of 0.862 > 0.05 and t count < t table (0.345 < 2.01063), Brand Image has no influence on WOM (Word Of Mouth) as evidenced by the results 0.732> 0.05 and t count < t table (0.345 < 2.01063), WOM (Word of Mouth) has no influence on purchasing decisions as evidenced by the results of 0.140> 0.05 and t count < t table (1.503 < 2.01063).